(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Selenium (Se), an essential trace element that is toxic when humans and animals are exposed to it in excess, is ubiquitous in coal. For centuries, superhigh-organic-sulfur (SHOS) Raša coal, enriched in S, Se, U, V, and Mo, was mined and processed across the Mediterranean Raša Bay area, located in the Istrian peninsula (in the northern Adriatic Sea, Croatia). There is concern that Raša coal mine water is contaminating local water, soil, and crops. The aim of this monitoring study was to determine the levels of Se and selected potentially toxic trace (As, Cd, Cu, Cr, Mo, Pb, U, V, and Zn), and minor (Fe and Mn) elements in Raša coal mine water, surface water, and associated vegetables, one fruit, and wild plants. Levels of Se in coal mine water were increased (up to 12 µg/L) compared to the maximum allowed water Se (10 µg/L). Compared to an EU average soil Se (1.15 mg/kg), Raša garden soil showed a 5-fold increase in Se. Compared to Croatian and Greek vegetable Se levels (low to normal), Raša vegetables showed a 20-fold, and a 50-fold increase in Se, respectively. Although approximative only, estimates of daily intake (EDI) of Se for mixed Raša vegetables (n = 21) showed a high level (0.055 mg/day). Namely, recommended dietary allowances (RDA) of Se for females and males are 0.055 mg/day, and 0.070 mg/day, respectively. The EDI values of the analyzed vegetables contributed to average RDA levels as follows: garlic (183%), turnip (154%), parsley (147%), onion and gourd (76%), lettuce (74%), kale (62%), radicchio (51%), and potato (20%). Although the calculated EDI for the analyzed Raša vegetables was 1/8 the toxic dose (>0.4 mg/day), these results call for further research on the dietary and nutritional status of the residents in terms of Se.